Global Regulation of Plant Immunity by Histone Lysine Methyl Transferases. Issue 7 (27th June 2016) - Lee, Sanghun; Fu, Fuyou; Xu, Siming; Lee, Sang Yeol; Yun, Dae-Jin; Mengiste, Tesfaye
Abstract : Arabidopsis histone methyl transferases SET DOMAIN GROUP8 and 25 regulate pep1-, flg22-, and effector-triggered immunity as well as systemic acquired resistance through regulation of the basal and induced transcriptome. Abstract: Posttranslational modification of histones modulates gene expression affecting diverse biological functions. We showed that the Arabidopsis thaliana histone methyl transferases SET DOMAIN GROUP8 (SDG8) and SDG25 regulate pep1-, flg22-, and effector-triggered immunity as well as systemic acquired resistance. Genome-wide basal and induced transcriptome changes regulated by SDG8 and/or SDG25 showed that two genes of the SDG-dependent transcriptome, CAROTENOID ISOMERASE2 ( CCR2 ) and ECERIFERUM3 ( CER3 ), were also required for plant immunity, establishing mechanisms in defense functions for SDG8 and SDG25. CCR2 catalyzes the biosynthesis of carotenoids, whereas CER3 is involved in the biosynthesis of cuticular wax. SDG8 and SDG25 affected distinct and overlapping global and locus-specific histone H3 lysine 4 (H3K4) and histone H3 lysine 36 (H3K36) methylations. Loss of immunity in sdg mutants was attributed to altered global and CCR2- and CER3-specific histone lysine methylation (HLM ). Loss of immunity in sdg, ccr2, and cer3 mutants was also associated with diminished accumulation of lipids and loss of cuticle integrity. In addition, sdg8 and sdg25 mutants were impaired in H2B ubiquitination (H2Bubn) at CCR2, CER3, and H2Bubn regulated R gene, SNC1, revealing crosstalk between the two types of histone modifications. In summary, SDG8 and SDG25 contribute to plant immunity directly through HLM or indirectly through H2Bubn and by regulating expression of plant immunity genes, accumulation of lipids, biosynthesis of carotenoids, and maintenance of cuticle integrity.